Mechanism of calcitriol regulating parathyroid cells in secondary hyperparathyroidism - Xiang, Zeli; Wang, Ming; Miao, Changxiu; Jin, Die; Wang, Hongyue (Frontiers in Pharmacology, 2022)
A common consequence of the chronic renal disease is secondary hyperparathyroidism (SHPT) and is closely related to the mortality and morbidity of uremia patients. Secondary hyperparathyroidism (SHPT) is caused by excessive PTH production and release, as well as parathyroid enlargement. At present, the mechanism of cell proliferation in secondary hyperparathyroidism (SHPT) is not completely clear. Decreased expression of VDR and CaSR, and calcitriol insufficiency all lead to a decrease in cell proliferation suppression, and activation of multiple pathways is also involved in cell proliferation in renal hyperparathyroidism. The interaction between the parathormone (PTH) and parathyroid hyperplasia and calcitriol has received considerable attention. Calcitriol is commonly applied in the therapy of renal hyperparathyroidism. It regulates the production of parathormone (PTH) and parathyroid cell proliferation through transcription and post-transcription mechanisms. This article reviews the role of calcitriol in parathyroid cells in secondary hyperparathyroidism and its current understanding and potential molecular mechanism.